2009
DOI: 10.1188/09.onf.519-524
|View full text |Cite
|
Sign up to set email alerts
|

Does Muscle-Derived Interleukin-6 Mediate Some of the Beneficial Effects of Exercise on Cancer Treatment-Related Fatigue?

Abstract: Purpose/Objectives To review evidence that muscle-derived interleukin-6 (IL-6) mediates some of the beneficial effects of exercise on cancer treatment–related fatigue (CTRF). Data Sources Electronic nursing, psychology, and medicine databases. Data Synthesis Fatigue is a common and often debilitating symptom associated with cancer treatment. Although the molecular mechanisms underlying CTRF have yet to be fully elucidated, it may be akin to the fatigue associated with “sickness behavior,” which is initiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 47 publications
1
14
0
2
Order By: Relevance
“…This has been in correlation with the elevated levels of tissue mRNA expression and circulating PTX 3 reported in a model of acute myocardial infarction which was explained by the role played by interleukin-1R-MyD88 in inducing PTX 3 transcript after ischemia. [12,41,42]. A significant increase of plasma PTX 3 was observed in group IV that were receiving flaxseed supplementation and on exercise (0.35±0.11ng/ml) as compared to group I the control group (0.15±0.04 ng/ml) and to group III that was on flaxseed supplementation only (0.18±0.12 ng/ml) (P< 0.001, P< 0.001 respectively).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This has been in correlation with the elevated levels of tissue mRNA expression and circulating PTX 3 reported in a model of acute myocardial infarction which was explained by the role played by interleukin-1R-MyD88 in inducing PTX 3 transcript after ischemia. [12,41,42]. A significant increase of plasma PTX 3 was observed in group IV that were receiving flaxseed supplementation and on exercise (0.35±0.11ng/ml) as compared to group I the control group (0.15±0.04 ng/ml) and to group III that was on flaxseed supplementation only (0.18±0.12 ng/ml) (P< 0.001, P< 0.001 respectively).…”
Section: Resultsmentioning
confidence: 92%
“…Recent research reported that moderate endurance activity influenced circulating cytokine levels specially the TNF- α levels which could be due to production of IL-6 produced by exercising muscle as an anti-inflammatory effect [41]. …”
Section: Resultsmentioning
confidence: 99%
“…Myofibrils also release mechano-growth factors, which impart autocrine effects on the muscle fibre. Relevant inflammatory biomarkers are catabolic biomarkers [18] and include cells involved in the cellular immune response, pro-inflammatory cytokines, such as ILs, IL-receptor antagonists (IL-RA), TNF-α [76] and other markers of inflammation [18]. …”
Section: Reviewmentioning
confidence: 99%
“…In 19 patients with CFS, who were studied during a 25 min cycling exercise to determine the amount of mRNA of metabolite-detecting genes (ASIC3, P2X4, P2X5), adrenergic genes (A2A, B-1, B-2, COMT) and immune system genes (IL-6, IL-10, TNF-α, TLR4, CD14), the activity of the genes encoding for ASIC3, P2X4, P2X5, B-1, B-2, COMT, IL-10, TLR4 and CD14 increased significantly in blood lymphocytes 30 min, 24 h and 48 h post-exercise [91]. The gene activity persistently increased between 0.5-48 h after exercise [91], suggesting that dysregulation of metabolite-detecting receptors occurs during fatigue [76,92]. In a study of subjects exposed to exhaustive exercise, both serum IL-6 and muscle IL-6 mRNA increased [93].…”
Section: Reviewmentioning
confidence: 99%
“…102 Furthermore, muscle-derived IL-6 has been proposed as a mechanism for the beneficial effects of exercise against cancer treatment-related fatigue. 103 …”
Section: Role Of Inflammatory Molecules In Cancer-related Symptomsmentioning
confidence: 99%